Fundamentals of accountancy, business, and management 2 - Camerino, Danilo S.; Acol, Arcadio B. (Makati City : Diwa Learning Systems Inc., 2020)
" Basic knowledge of accountancy is an advantage regardless of which field you eventually pursue in your studies. It bears practical significance as it places you in a position to better handle your finances to serve your best purposes. This textbooks aims to deepen your understanding of the basic skills in accounting and provide you with in-depth practice set to hone such skills. It helps you understand how financial records are managed and how business decisions and transactions impact the financial health of an organization."
Includes bibliography.
English text.
Keywords: Business; Accounting; Management